COVID-19 Epidemic: Chloroquine, a French Obsession? - Lapostolle, Fréderic (La Presse Médicale Open, 2021)
INTRODUCTION: One potential COVID-19 treatment, hydroxychloroquine has been the focus of much debate since its first publication by a French research team. To an unusual degree, this debate has extended outside of the medical community into the public sphere. OBJECTIVE: To know if this interest, which conceals the reality of scientific debate, occurred worldwide. METHODS: Methodological use of the Google-Trends was standardized. We researched the web queries for “hydroxychloroquine” and “chloroquine” and “amoxicillin” and “acetaminophen” as reference. Analysis was detailed by country. The relationship between these queries and the COVID-19 epidemic was supported by analysis of the main “related queries”. Google-Trends provided results on a relative value basis, on a scale from 0 to 100, with a value of 100 indicating the most researched criterion over the study period. RESULTS: Web queries for “amoxicillin” never exceeded the value of 1. Searches for “acetaminophen” peaked on March 13 with a value of 13. “Hydroxychloroquine” was the most frequently researched term. It reached its peak value of 99 on April 7. Queries for “chloroquine” peaked (value 100) on March 24. Searches for “hydroxychloroquine” came essentially from Asia and the United States, with France in 22(nd) position (value of 21). Searches for “chloroquine” came essentially from Africa, with France in 8(th) position (value of 55). The five main related searches were in both cases associated with the COVID-19 epidemic. CONCLUSION: Interest in chloroquine is not specific to France. Results of ongoing studies have been and will be scrutinized attentively in all corners of the globe.